Influence of Air Abrasion and Sonic Technique on Microtensile Bond Strength of One-Step Self-Etch Adhesive on Human Dentin - Baraba Anja; Dukić Walter; Chieffi Nicoletta; Ferrari Marco; Sonja Pezelj Ribarić; Miletić Ivana (The Scientific World Journal)
The purpose of this in vitro study was to evaluate the microtensile bond strength of one-step self-etch adhesive to human dentin surface modified with air abrasion and sonic technique and to assess the morphological characteristics of the pretreated dentin surface. The occlusal enamel was removed to obtain a flat dentin surface for thirty-six human molar teeth. The teeth were randomly divided into three experimental groups (n = 12 per group), according to the pretreatment of the dentin: (1) control group, (2) air abrasion group, and (3) sonic preparation group. Microtensile bond strength test was performed on a universal testing machine. Two specimens from each experimental group were subjected to SEM examination. There was no statistically significant difference in bond strength between the three experimental groups (P > 0.05). Mean microtensile bond strength (MPa) values were 35.3 ± 12.8 for control group, 35.8 ± 13.5 for air abrasion group, and 37.7 ± 12.0 for sonic preparation group. The use of air abrasion and sonic preparation with one-step self-etch adhesive does not appear to enhance or impair microtensile bond strength in dentin.